2016
DOI: 10.1371/journal.pone.0168119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transient and Persistent Acute Kidney Injury on Chronic Kidney Disease Progression and Mortality after Gastric Surgery for Gastric Cancer

Abstract: Acute kidney injury (AKI) is common after gastric surgery for gastric cancer and associated with adverse outcomes. However, the impact of transient or persistent AKI on clinical outcomes after gastric surgery for gastric cancer has not been described. We performed a retrospective study of 4,886 patients with normal renal function who underwent partial or total gastrectomy for gastric cancer between June 2002 and December 2012. AKI patients were classified as transient and persistent AKI based on the return of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Furthermore, there is also an association between AKI duration and long-term outcomes [26]. In a recent metaanalysis of 18 studies by Mehta et al [27], there was an association between longer duration of AKI and longterm outcomes, namely, mortality, cardiovascular outcomes, and progression to CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is also an association between AKI duration and long-term outcomes [26]. In a recent metaanalysis of 18 studies by Mehta et al [27], there was an association between longer duration of AKI and longterm outcomes, namely, mortality, cardiovascular outcomes, and progression to CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have brought attention to the duration of AKI as an important component affecting clinical outcomes. pAKI is associated with even more severe patient outcomes when compared with transient AKI or no AKI, such as development of progressive chronic kidney disease, increased in‐hospital mortality, and reduced long‐term survival . Perinel and colleagues reported that pAKI developed in 39% of ICU patients (175 of 447) and that it was associated with a higher in‐hospital mortality (38.9%) compared with transient AKI (29.6%) and no AKI (23.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Perinel and colleagues reported that pAKI developed in 39% of ICU patients (175 of 447) and that it was associated with a higher in‐hospital mortality (38.9%) compared with transient AKI (29.6%) and no AKI (23.8%). In patients undergoing elective gastric surgery, Kim et al reported that only a small percentage of patients (1.3%) had pAKI. However, pAKI led to significant in‐hospital mortality (12.5%) and 1‐year mortality (18.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of 13 cohort studies, Cocaet al showed that AKI patients had significantly higher risks of developing CKD and end stage renal disease (ESRD) and higher mortality as compared to the patients without AKI 11 . More recently, Kim et al reported that persistent AKI (defined as incomplete reduction of serum creatinine at 7 days) after gastric surgery was associated with CKD progression 1 year later 12 . Similarly, the duration of AKI after cardiac surgery was also regarded as a strong independent risk factor for CKD development 13 .…”
Section: The Aki-ckd Connectionmentioning
confidence: 99%